2016
DOI: 10.1002/ppap.201600164
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Surface Mode Influence on Plasma Uniformity in PIC/MCC Simulations of Large Capacitive Discharges

Abstract: Capacitively coupled plasmas with large electrodes, driven at high frequencies, exhibit new physics compared to small scale CCP devices or at low frequencies. This is due to excitation of two types of surface modes which arise as a result of interaction between the bulk plasma and the plasma sheaths separating the plasma from electrodes. Based on the physical effects that these modes cause, they are labeled as “self‐bias” (SB) and “plasma‐series resonance” (PSR) modes. Results of electrostatic 2d3v PIC/MCC sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
(97 reference statements)
0
16
0
2
Order By: Relevance
“…The impact of external circuits is not our primary interest in the present work. Although previous studies observed symmetric and asymmetric structures through 2D PIC simulations, [ 9–15,17,18 ] they did not observe nonlocal kinetic effects by particle dynamics sensitive to the time change. The previous study for the nonlocal effect observed time‐averaged and spatiotemporal profiles for a specific pressure condition of 100 mTorr.…”
Section: Simulation Conditionsmentioning
confidence: 79%
See 1 more Smart Citation
“…The impact of external circuits is not our primary interest in the present work. Although previous studies observed symmetric and asymmetric structures through 2D PIC simulations, [ 9–15,17,18 ] they did not observe nonlocal kinetic effects by particle dynamics sensitive to the time change. The previous study for the nonlocal effect observed time‐averaged and spatiotemporal profiles for a specific pressure condition of 100 mTorr.…”
Section: Simulation Conditionsmentioning
confidence: 79%
“…Studies on various kinetic effects in 2D CCP structures have recently been reported, even for high‐pressure regimes. [ 7, 9–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a constant rf power has led to unstable results in our simulation. In addition, most researchers 27,[32][33][34] conducted PIC/MCC simulations with a fixed rf voltage or current and not rf power.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Using an electrostatic implicit particle-in-cell (PIC) code, Eremin et al found that a high frequency driven large-area capacitively coupled plasma (CCP) discharge can exhibit strong wave effects [52]. They also demonstrated that the two types of wave modes lead to non-uniformities of the plasma density profile [58], and that large collisionality gives rise to a strong damping of the waves as they propagate [53].…”
Section: Introductionmentioning
confidence: 99%